2003
DOI: 10.1128/jvi.77.24.12950-12960.2003
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Morphology Comparisons of Self-AssembledVirus-Like Particles from Wild-Type and Mutant Human Hepatitis B VirusCapsidProteins

Abstract: Instead of displaying the wild-type selective export of virions containing mature genomes, human hepatitis B virus (HBV) mutant I97L, changing from an isoleucine to a leucine at amino acid 97 of HBV core antigen (HBcAg), lost the high stringency of selectivity in genome maturity during virion export. To understand the structural basis of this so-called "immature secretion" phenomenon, we compared the stability and morphology of self-assembled capsid particles from the wild-type and mutant I97L HBV, in either f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 37 publications
6
70
0
1
Order By: Relevance
“…Multiangle laser light scattering data were consistent with assignment of the two peaks as the 4-MDa capsid and 34-kDa dimer (data not shown). In agreement with other reports (19), Cp149-F97L and -wt capsids were indistinguishable by negative-stain electron microscopy and on sucrose gradients (data not shown).…”
Section: Resultssupporting
confidence: 82%
“…Multiangle laser light scattering data were consistent with assignment of the two peaks as the 4-MDa capsid and 34-kDa dimer (data not shown). In agreement with other reports (19), Cp149-F97L and -wt capsids were indistinguishable by negative-stain electron microscopy and on sucrose gradients (data not shown).…”
Section: Resultssupporting
confidence: 82%
“…C), a clear band could be seen in the both the Coomassie-and ethidium bromide-stained gels. The two signals had the same electrophoretic mobility, suggesting that the VLP protein core, stained by the Coomassie, encapsidated nucleic acids, stained by ethidium bromide, consistent with previous reports (Newman et al, 2003). The presence of intact VLPs was further confirmed by TEM images (Figure 1.…”
Section: Purification and Analysis Of Plant-expressed Hbcagsupporting
confidence: 75%
“…This result is in accordance with Newman et al (2003): in that case, it was shown that bacterially expressed HBcAg incubated at pH 2.0 for only 30 minutes was unstable and it remained blocked in the well (Newman et al, 2003). Overall, in the current study, the native agarose gel electrophoresis revealed that this complete loss of the physical stability upon incubation of HBcAg for two hours in acid and further neutralisation occurs at pH values below 3 to 3.5 (Figure 3).…”
supporting
confidence: 77%
“…This is well supported by Figure 4b, showing that the fastest decrease of fluorescent intensity was observed in tumor cells treated with mC out ‐HBVC, while the slowest was with mC in ‐HBVC. It seems that the low‐pH‐degradable mCardinal11 was effectively protected when it was encapsulated within the HBVC that is known to be stable over a wide range of pH (4–10) 21…”
Section: Resultsmentioning
confidence: 99%